Mill and Tocqueville: a friendship bruised. Issue 1 (2nd January 2016) - Suh, Byung-Hoon
SUMMARY: Having first met in 1835, John Stuart Mill and Alexis de Tocqueville began 'an extremely interesting and mutually laudatory correspondence'; but their splendid friendship did not last. A popular thesis focuses on letters exchanged in 1840 to 1842 that reflect conflicting views on the Eastern Question and argues that Mill initiated the 'strange interruption'. Given Mill's commitment to the 'agreement of conviction and feeling on the few cardinal points of human opinion' as a prerequisite of genuine friendship, such interpretation sounds plausible. However, circumstantial evidence, most notably Mill's willingness to have a frank discussion with Tocqueville on pending issues, contradicts the assertion that Mill was enraged by Tocqueville's 1841 letter. This essay suggests focusing attention on two additional cardinal differences between them—their contrasting views of François Guizot and confrontation vis-à-vis benevolent imperialism. Moreover, personal matters such as Harriet Taylor's dislike of Tocqueville and Mill's departure from the London and Westminster Review are also believed to have largely led to Mill discontinuing correspondence with Tocqueville.